OBLIGATION OF A PATIENT TO HIS HEALTH AS THE CONDITION OF THE RIGHT TO HEALTHCARE SERVICES - Januševičienė, Justina (Teisė, 2017)
This article focuses on the complexity of the obligation of a patient to his health and aims to approach it as one of the most important conditions of patient‘s rights instead of regarding it as a declarative note to a patient. Social pressure binding an individual to fulfil certain obligations arise only in case legal provisions are considered as important and essential for sustainability of social life.